2015
DOI: 10.1515/cclm-2015-0923
|View full text |Cite
|
Sign up to set email alerts
|

Analytical and clinical evaluation of the new Fujirebio Lumipulse®G non-competitive assay for 25(OH)-vitamin D and three immunoassays for 25(OH)D in healthy subjects, osteoporotic patients, third trimester pregnant women, healthy African subjects, hemodialyzed and intensive care patients

Abstract: Fujirebio Lumipulse®G 25-OH Vitamin D Total assay is therefore considered suitable for assessment of vitamin D status in clinical routine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 23 publications
3
18
0
Order By: Relevance
“…Compared to competing immunoassays, the new 5P02 assay presents a better agreement with the LC-MS/MS, in the global population, but also especially in osteoporotic patients and in patients from the intensive care unit. Unfortunately, we did not have the opportunity to compare the performances of the 5P02 assay to the Fujirebio Lumipulse we recently validated and which is the only sandwich method available for 25(OH)D. Indeed, our results had shown that this assay presented a much improved clinical concordance compared to the other "classical" competitive immunoassays [11].…”
Section: Discussionmentioning
confidence: 93%
“…Compared to competing immunoassays, the new 5P02 assay presents a better agreement with the LC-MS/MS, in the global population, but also especially in osteoporotic patients and in patients from the intensive care unit. Unfortunately, we did not have the opportunity to compare the performances of the 5P02 assay to the Fujirebio Lumipulse we recently validated and which is the only sandwich method available for 25(OH)D. Indeed, our results had shown that this assay presented a much improved clinical concordance compared to the other "classical" competitive immunoassays [11].…”
Section: Discussionmentioning
confidence: 93%
“…If we consider 30 nmol/L as the threshold for hypovitaminosis D, the question is whether we can apply this threshold using every current method (mostly automated immunoassays)? Comparisons among and between methods show a bias of several immunoassays compared to LC-MS/ MS methodologies [31][32][33][34].…”
Section: Threshold For Defining Vitamin D Deficiency/insufficiency Wimentioning
confidence: 99%
“…Several studies have evaluated and compared 25(OH)D assays. Though the methods overall correlated well, substantial variability between assays was found [12][13][14][15][16]. Some of these studies were performed early after the initiation of the VDSP initiative where standardization of assays…”
Section: Brief Resumé Of the Resultsmentioning
confidence: 99%